Ecomorphodynamics of rivers with converging boundaries. Issue 12 (8th August 2014) - Perona, Paolo; Crouzy, Benoît; McLelland, Stuart; Molnar, Peter; Camporeale, Carlo
ABSTRACT Many rivers worldwide show converging sections where a characteristic limiting front for vegetation establishment on gravel bars is observed. An important conceptual model was advanced in 2006 by Gurnell and Petts, who demonstrated that for the convergent section of the Tagliamento River the downstream front of vegetation establishment can be explained by unit stream power. We introduce a theoretical framework based on 1D ecomorphodynamic equations modified to account for the biological dynamics of vegetation. We obtain the first analytical result explaining the position and river width where vegetation density is expected to vanish in relation to a characteristic streamflow magnitude and both hydraulic and biological parameters. We apply our model to a controlled experiment within a convergent flume channel with growing seedlings perturbed by periodic floods. For a range of timescales where hydrological and biological processes interact, we observe the formation of a front in the convergent section beyond which vegetation cannot survive, the location of which is explained by flow magnitude. This experiment confirms that the timescales of the involved processes and the unit stream power determine the existence and the position of the front within convergent river reaches, respectively. Copyright © 2014 John Wiley & Sons, Ltd.